936 - Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: dept.hms

Marathon and ultra-endurance performance - Lunn, William R. (Medicine & Science in Sports & Exercise, 2023)
Num Pages: 1
Keywords: dept.hms; peer-reviewed

Body Composition Evaluation During The Competitive Season Of An NCAA Division II Men's Soccer Team - Lunn, William; Axtell, Robert (Medicine & Science in Sports & Exercise, 2025)
Keywords: Athletes; Body fat percentage; Competitive athletes; Composition (language); Division (mathematics); Fat mass; Lean body mass; Team sport; dept.hms

Effect Of Creatine Monohydrate Supplementation On VO2 Kinetics In Aerobically Fit Adults - Raymond, Emerson; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Blood lactate; Creatine; Crossover study; Heart rate; Lactate threshold; Percentile; Treadmill; VO2 max; Ventilatory threshold; dept.hms

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test - Lunn, William R.; Axtell, Robert S. (The Journal of Strength & Conditioning Research, 2019)
Lunn, WR and Axtell, RS. Validity and reliability of the Lode Excalibur Sport cycle ergometer for the Wingate Anaerobic Test. J Strength Cond Res XX(X): 000–000, 2019—Although multiple testing devices advertise Wingate Anaerobic Test (WAnT), capability, reliability, and validity data are sparse. The purpose was to determine whether the Lode Excalibur Sport cycle ergometer is a reliable and valid instrument to conduct the 30-second WAnT when compared with the Monark 894e Peak Bike ergometer. Recreationally active men (n = 49; 20.6 ± 2.5 years; 1.75 ± 0.07 m; and 79.1 ± 9.8 kg) completed four 30-second WAnTs: 2 each on the Lode and the Monark ergometers for peak power (PP), mean power (MP), minimum power (MinP), fatigue index (FI), and peak cadence (vmax) measurement. Interday and interunit correlation, multivariate analysis of variance, regression, and Bland-Altman analysis determined reliability and validity. Cohen's d was used to determine effect size. Relative reliability (intraclass correlation coefficient) with 95% confidence interval for Monark and Lode was very high for PP, MP, MinP, and vmax and high for FI (r > 0.83; coefficient of variation ≤ 27.0%; p < 0.01). Interunit correlation was strong for PP, MP, MinP, and vmax (r > 0.75; p < 0.001) and moderate for FI (p = 0.001). Lode PP and FI values were significantly less (p < 0.001; d > 1.18) and MinP, MP, and vmax significantly greater (p ≤ 0.001; d > 0.51) than Monark. Proportional bias was demonstrated for all variables (p < 0.04; d > 2.68) except vmax. The Lode ergometer reliably provides WAnT outcomes and correlates well to the Monark ergometer. However, differences in power values and proportional bias between differently braked instruments prevent use of the Lode ergometer for comparison of WAnT data with normative data generated by the Monark ergometer.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lunnValidityReliabilityLode2019
Keywords: dept.hms; peer-reviewed

Similar Relative Energy Deficiency In Sport (REDs) Variables In Men And Women NCAA Distance Runners - Bryan, J.; Rupp, Kristie; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Basal metabolic rate; Bone mineral; Doubly labeled water; Dual energy; Energy expenditure; Energy metabolism; Fat free mass; Fat mass; Physical activity; dept.hms

Effects of sprint interval training and body weight reduction on power to weight ratio in experienced cyclists. - Lunn, William R; Finn, Joan A; Axtell, Robert S (Journal of strength and conditioning research, 2009)
The purpose of this study was to determine the effect of supramaximal sprint interval training (SIT), body weight reduction, and a combination of both treatments on peak and average anaerobic power to weight ratio (PPOan:Wt, APOan:Wt) by manipulating peak and average anaerobic power output (PPOan, APOan) and body weight (BW) in experienced cyclists. Participants (N = 34, age = 38.0 +/- 7.1 years) were assigned to 4 groups for a 10-week study. One group performed twice-weekly SIT sessions on a cycle ergometer while maintaining body weight (SIT). A second group did not perform SIT but intentionally reduced body weight (WR). A third group simultaneously performed SIT sessions and reduced body weight (SIT+WR). A control group cycled in their normal routine and maintained body weight (CON). The 30-second Wingate Test assessed pretest and posttest POan:Wt scores. There was a significant mean increase (p < 0.05) from pretest to posttest in PPOan:Wt and APOan:Wt (W x kg(-1)) scores in both SIT (10.82 +/- 1.71 to 11.92 +/- 1.77 and 8.05 +/- 0.64 to 8.77 +/- 0.64, respectively) and WR (10.33 +/- 2.91 to 11.29 +/- 2.80 and 7.04 +/- 1.45 to 7.62 +/- 1.24, respectively). PPOan and APOan (W) increased significantly only in SIT (753.7 +/- 121.0 to 834.3 +/- 150.1 and 561.3 +/- 62.5 to 612.7 +/- 69.0, respectively). Body weight (kg) decreased significantly in WR and SIT + WR (80.3 +/- 13.7 to 75.3 +/- 11.9 and 78.9 +/- 10.8 to 73.4 +/- 10.8, respectively). The results demonstrate that cyclists can use SIT sessions and body weight reduction as singular training interventions to effect significant increases in anaerobic power to weight ratio, which has been correlated to enhanced aerobic cycling performance. However, the treatments were not effective as combined interventions, as there was no significant change in either PPOan:Wt or APOan:Wt in SIT + WR.
7 citations (Crossref) [2023-10-31] Place: United States Lunn, William R. Exercise Science Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. wlunn25@comcast.net
Keywords: *Bicycling/ph [Physiology]; *Physical Education and Training/mt [Methods]; *Weight Loss; Adult; Analysis of Variance; Bicycling; Body Composition; Body Mass Index; Body Weight; Female; Humans; Male; Physical Education and Training; Physical Endurance; Physical Endurance/ph [Physiology]; Reproducibility of Results; Weight Loss; Wingate test; adult; analysis of variance; article; bicycle; body composition; body mass; body weight; dept.hms; endurance; female; human; male; methodology; peer-reviewed; physical education; physiology; reproducibility; weight reduction

Cannabidiol supplementation alleviates anxiety, mitigates pain, extends endurance, and facilitates greater exercise exertion: 277 - Lunn, William R.; Axtell, Robert S. III; Venard, Anna; Bodurtha, Phillip; Brunello, Greta; Bukowski, Zachary (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Chocolate milk and endurance exercise recovery: protein balance, glycogen, and performance. - Lunn, William R; Pasiakos, Stefan M; Colletto, Megan R; Karfonta, Kirstin E; Carbone, John W; Anderson, Jeffrey M; Rodriguez, Nancy R (Medicine and science in sports and exercise, 2012)
Purpose: This study examined effects of fat-free chocolate milk (MILK) consumption on kinetic and cellular markers of protein turnover, muscle glycogen, and performance during recovery from endurance exercise. Methods: Male runners participated in two trials separated by 1 wk and consumed either MILK or a nonnitrogenous isocaloric carbohydrate (CHO) control beverage (CON) after a 45-min run at 65% of V̇O 2peak. Postexercise muscle protein fractional synthetic rate (FSR) and whole-body protein turnover were determined during 3 h of recovery using muscle biopsies and primed constant infusions of L-[ring-H5]phenylalanine and L-[1-C]leucine, respectively. Phosphorylation of translational signaling proteins and activity of proteolytic molecules were determined using Western blotting and enzymatic activity assays. Muscle glycogen was quantified, and treadmill time to exhaustion was determined after the recovery period. Results: Consuming MILK after exercise resulted in higher mixed muscle FSR with lower whole-body proteolysis and synthesis compared with CON (P ≤ 0.05). Phosphorylation of eIF4E-BP1 and FOXO3a was higher for MILK (P < 0.01), whereas Akt phosphorylation was lower during recovery regardless of dietary treatment (P < 0.05). Enzymatic activity assays indicated lower caspase-3 activity during recovery for MILK (P < 0.01) and higher 26S proteasome activity for CON (P < 0.01). Muscle glycogen was not affected by either dietary treatment; however, time to exhaustion was greater for MILK than for CON (P < 0.05). Conclusions: The effects of consumption of MILK after endurance exercise on FSR, signaling molecules of skeletal muscle protein turnover, leucine kinetics, and performance measures suggest unique benefits of milk compared with a CHO-only beverage. © 2012 by the American College of Sports Medicine.
66 citations (Crossref) [2023-10-31] Place: United States Lunn, William R. Exercise Science Department, Southern Connecticut State University, Moore Field House, Room 169, New Haven, CT 06515, USA. lunnw1@southernct.edu
Keywords: *Athletic Performance/ph [Physiology]; *Cacao/me [Metabolism]; *Milk/me [Metabolism]; *Muscle Proteins/bi [Biosynthesis]; *Physical Endurance/ph [Physiology]; ATP dependent 26S protease; Adaptor Proteins; Signal Transducing; Adaptor Proteins; Signal Transducing/me [Metabolism]; Adult; Animals; Athletic Performance; Cacao; Cell Cycle Proteins; Dietary Carbohydrates; Dietary Carbohydrates/me [Metabolism]; EIF4EBP1 protein; human; FOXO3 protein; human; Forkhead Box Protein O3; Forkhead Transcription Factors; Forkhead Transcription Factors/me [Metabolism]; Glycogen; Glycogen/an [Analysis]; Heart Rate; Heart Rate/ph [Physiology]; Humans; Male; Milk; Muscle Proteins; Muscle; Skeletal; Muscle; Skeletal/ch [Chemistry]; Muscle; Skeletal/me [Metabolism]; Muscle; Skeletal/ph [Physiology]; Oxygen Consumption; Oxygen Consumption/ph [Physiology]; Phosphoproteins; Phosphoproteins/me [Metabolism]; Phosphorylation; Physical Endurance; Proteasome Endopeptidase Complex; Proteasome Endopeptidase Complex/an [Analysis]; Protein synthesis; Proto-Oncogene Proteins c-akt; Proto-Oncogene Proteins c-akt/me [Metabolism]; Young Adult; adult; animal; article; athletic performance; biosynthesis; cacao; carbohydrate diet; chemistry; dept.hms; endurance; forkhead transcription factor; glycogen; heart rate; human; intracellular signaling; leucine kinetics; male; metabolism; milk; muscle glycogen; muscle protein; oxygen consumption; peer-reviewed; phosphoprotein; phosphorylation; physiology; proteasome; protein kinase B; proteolysis; signal transducing adaptor protein; skeletal muscle; time to exhaustion

The effect of high dose creatine supplementation on thermoregulatory adaptation during a standard heat acclimation protocol - Martin, David; Thornton, Staci; Langan, Seam; Navarro, John; Brewer, Gabrielle; Szymanski, Michael; Huggins, Robert; Lunn, William; Rodriguez, Nancy; Casa, Douglas; Lee, Elaine (Medicine & Science in Sports & Exercise, 2025)
Keywords: Acclimatization; Analysis of variance; Core temperature; Creatine; Dehydration; Heat stress; Rectal temperature; Thermoregulation; dept.hms